Historical first descriptions of Cajal–Retzius cells: from pioneer studies to current knowledge - Gil , Vanessa; Nocentini, Sara; del Río, José A. (Frontiers in Neuroanatomy, 2014)
Santiago Ramón y Cajal developed a great body of scientific research during the last decade of 19th century, mainly between 1888 and 1892, when he published more than 30 manuscripts. The neuronal theory, the structure of dendrites and spines, and fine microscopic descriptions of numerous neural circuits are among these studies. In addition, numerous cell types (neuronal and glial) were described by Ramón y Cajal during this time using this ‘reazione nera’ or Golgi method. Among these neurons were the special cells of the molecular layer of the neocortex. These cells were also termed Cajal cells or Retzius cells by other colleagues. Today these cells are known as Cajal-Retzius cells. From the earliest description, several biological aspects of these fascinating cells have been analyzed (e.g., cell morphology, physiological properties, origin and cellular fate, putative function during cortical development, etc). In this review we will summarize in a temporal basis the emerging knowledge concerning this cell population with specific attention the pioneer studies of Santiago Ramón y Cajal.